Primary School Teachers’ Perception of Supervision Through the Use Google Form Application During the Covid-19 Pandemic - Nining Purwati; Mohammad Viktor Farid Hakim (STAI Hubbulwathan Duri, 2021)
This study aimed to investigate the teachers’ perception and supervision experience using the google-form application during the Covid-19 pandemic. The research method used a qualitative approach with a descriptive method. Data were collected by using observation, questionnaires and interviews. There were 10 participants (male 5 and female 5). They were teachers (8 teachers), vice-principal of the curriculum and principal. The process of data analysis is through data reduction, data presentation, drawing conclusions and triangulation. The study results concluded that the google-form provides convenience in examining teachers' teaching and learning files. It was easy for school principals to assess the results of teacher teaching with a longer period before the implementation of online supervision, as an advanced form of using the google-form. The study results also had implications for teachers and school principals' understanding of the use of technology applications to improve teaching and learning or provide higher quality education.